Effects of Shrinkage-Compensation on Mechanical Properties and Repair Performance of Strain-Hardening Cement Composite Materials - Seok-Joon Jang; Sun-Woo Kim; Wan-Shin Park; Koichi Kobayashi; Hyun-Do Yun (Advances in Civil Engineering)
This paper describes the effects of expansive admixture on the mechanical properties of strain-hardening cement-based composite (SHCC) mixtures. Also, this study investigates structural performance of reinforced concrete (RC) beam specimens repaired with SHCC and Ex-SHCC (SHCC with expansive admixture). In this study, SHCC and Ex-SHCC mixtures with two specified compressive strength values of 30 MPa and 60 MPa and the fiber volume fraction of 1.5% were investigated. The expansive admixture replacement ratio of 10% by cement weight was used in this study. The test results indicate that the compressive, tensile, and flexural strength values of the SHCC mixtures increased when expansive admixture was included in the mix; however, their toughness and ductility decreased. The study results also show that the application of both SHCC and Ex-SHCC mixtures to repair damaged RC beam specimens can lead to significant structural performance improvement by mitigating crack damage and increasing ductility.